Post-Lumbar Puncture Chronic Intracranial Subdural Hematoma - Mathew, Sherman David; Abraham, Betsy (International Journal of Integrated Health Sciences, 2019)
Objective: To desribe a case of cranial subdural hematoma as an atypically sporadic and potentially devastating complication of a lumbar puncture mimicking post-dural puncture headache which may lead to delayed diagnosis.Method: This is a a case report of chronic intracranial subdural hematoma as a complication of lumbar puncture for spinal anaesthesia in a forty-eight-year-old male underwent an uneventful ureterolithotomy. In the postoperative period, the patient complained of excruciating headache which partially subsided with symptomatic treatment. However, after four weeks, the patient presented with worsening headache and Â vomiting.Results: A contrast enhanced computer tomography study revealed a subdural haematoma in the left fronto-temporo-parietal-region. The patient underwent an immediate decompressive craniectomy for subdural hematoma. The postoperative period was Â uneventful and the patient was discharged without any neurological deficits.Conclusion: Intracranial complication such as subdural hematoma is rare after a dural puncture and is often masquerading as a post dural puncture headache. Imaging studies like computerized tomography and magnetic resonance imaging are to be considered in earlier stages of non-retractable headache to rule out such rare complications.